OPTIMIZATION OF DIAGNOSTIC AND TREATMENT METHODS ACUTE ABSCESSES AND GANGRENA OF LUNGS IN PATIENTS WITH DIABETES - Bobobekov , A.R. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2022)
Effective treatment for acute suppuchy destructive lung diseases and diabetes mellitus is a topical application of antibacterial drugs in large doses by proolong select intraarial catheter therapy. When pleleal complications should expand the indices for drainage.